The association of periodontitis and metabolic syndrome - Abhijit N Gurav (Wolters Kluwer Medknow Publications, 2014)
Metabolic syndrome (MS) is a condition, which constitutes a group of risk factors that occur together and increase the risk for Coronary Artery Disease, Stroke and type 2 diabetes mellitus. This disorder is found prevalent in the industrialized societies of the world in epidemic proportions. Periodontitis is an oral disease of microbial origin characterized by loss of attachment apparatus of tooth, resulting in edentulism if untreated. Periodontitis has been attributed to produce a low grade systemic inflammatory condition. The link of periodontitis to various systemic disorders has led to the evolution of a new branch termed as "periodontal medicine." Studies reviewed in the present paper have indicated a positive link between the MS and periodontitis and it is suggested that subjects displaying several components of MS should be submitted to periodontal examination. Present studies have displayed coherent relation between the two entities. This review will address the vicious association between MS and periodontitis, depicting the commonality of pathophysiological pathway between the two entities. Systematic reviews, meta-analysis addressing the concerned subject were screened. Whether the systematic periodontal therapy in individuals exhibiting MS has the potential to reduce the incidence of various adverse systemic complications remains a logical proposition. Further, longitudinal and controlled trials with a large population would be imperative to depict the robustness in the association between MS and periodontal disease in human subjects.